Validation of Plasmodium vivax centromere and promoter activities using Plasmodium yoelii. - Kittisak Thawnashom; Miho Kaneko; Phonepadith Xangsayarath; Nattawat Chaiyawong; Kazuhide Yahata; Masahito Asada; John H Adams; Osamu Kaneko (PLoS ONE)
Plasmodium vivax is the leading cause of malaria outside Africa and represents a significant health and economic burden on affected countries. A major obstacle for P. vivax eradication is the dormant hypnozoite liver stage that causes relapse infections and the limited antimalarial drugs that clear this stage. Advances in studying the hypnozoite and other unique biological aspects of this parasite are hampered by the lack of a continuous in vitro laboratory culture system and poor availability of molecular tools for genetic manipulation. In this study, we aim to develop molecular tools that can be used for genetic manipulation of P. vivax. A putative P. vivax centromere sequence (PvCEN) was cloned and episomal centromere based plasmids expressing a GFP marker were constructed. Centromere activity was evaluated using a rodent malaria parasite Plasmodium yoelii. A plasmid carrying PvCEN was stably maintained in asexual-stage parasites in the absence of drug pressure, and approximately 45% of the parasites retained the plasmid four weeks later. The same retention rate was observed in parasites possessing a native P. yoelii centromere (PyCEN)-based control plasmid. The segregation efficiency of the plasmid per nuclear division was > 99% in PvCEN parasites, compared to ~90% in a control parasite harboring a plasmid without a centromere. In addition, we observed a clear GFP signal in both oocysts and salivary gland sporozoites isolated from mosquitoes. In blood-stage parasites after liver stage development, GFP positivity in PvCEN parasites was comparable to control PyCEN parasites. Thus, PvCEN plasmids were maintained throughout the parasite life cycle. We also validated several P. vivax promoter activities and showed that hsp70 promoter (~1 kb) was active throughout the parasite life cycle. This is the first data for the functional characterization of a P. vivax centromere that can be used in future P. vivax biological research.